Regional Law and Policy in Encouraging Community Participation in Sustainable Environmental Management - Moh.Taufik; Sugiyanto Sugiyanto; Soesi Idayanti; Sanusi Sanusi; Moh.Wildan (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2026)
Community participation has become an essential element in environmental planning and management, particularly in addressing climate change risks and environmental degradation. Global experiences indicate that meaningful public involvement can strengthen local resilience and support sustainable development by ensuring that environmental policies are effective, equitable, and responsive to community needs. However, the implementation of participatory policies at the regional level still faces various challenges, including limited access to information, insufficient community capacity, inequality in deliberative processes, and local political influences. This study aims to analyze legal instruments and strategic measures adopted by regional governments in encouraging community participation for long-term environmental conservation. This research employs a library research method with a normative juridical approach through theoretical legal analysis of relevant regulations, policies, and academic literature. The findings show that regional policies have an important role in transforming public participation from a procedural requirement into meaningful engagement that influences environmental decision-making. The implementation of Constitutional Court Decision No. 91/PUU-XVIII/2020 concerning the Job Creation Law provides an opportunity to strengthen public oversight of environmental governance and conservation policies. The study concludes that systemic reform in environmental management, including the improvement of Environmental Impact Assessment (AMDAL) mechanisms, requires active collaboration and involvement from all sectors of society to achieve sustainable ecological protection.